THE IMPACT OF FAST FASHION ON THE DEVELOPMENT OF LOCAL FASHION BRANDS IN BANDA ACEH - fitriana, fitriana; Salsabilla, Dinda; Prayudha, Agung Rorhi (Universitas Negeri Yogyakarta, 2025)
The rise of new trends in the fashion industry, particularly fast fashion, has accelerated the fashion cycle's pace. Fast fashion is a trend ained at following the latest styles and attracting consumers with low prices. This study aims to determine the influence of fast fashion on the marketing of local fashion brands in Banda Aceh, the devolopment of fashion among university students, and the impact of fast fashion on student concumerism culture. The study employs a quanitative research method with o correlational approach, using a sample of 63 Fashion Desigh students selected based on Slovin's formula. Data were collected online and analyzed using Likert Scale. The results, based on the Pearson produk-moment correlation test, indicate that fast fashion has a significant influence on the marketing and devolopment of local fashion brand in Banda Aceh. The concumerism cilture among students, who tend to prefer fast fashion products, is influenced by several factors, including relatively lover prices and the technplogical expansion of online sales through e-commerce platforms widely used today. The students' economic condition, primarily relying on allowances from their parents, also play a role. Despite facing challenges in pricing and production capacity, local brands in Banda Aceh have significant opportunities to grow by leveraging sustainable fashion trends. Local brands must remain competitive in production and marketing strategies and collaborate with the government anf other stakeholders to support the development of local products.